2009
DOI: 10.1051/0004-6361/200911694
|View full text |Cite
|
Sign up to set email alerts
|

PHL 5038: a spatially resolved white dwarf $\mathsf{+}$ brown dwarf binary

Abstract: A near-infrared excess is detected at the white dwarf PHL 5038 in UKIDSS photometry, consistent with the presence of a cool, substellar companion. We have obtained H-and K-grism spectra and images of PHL 5038 using NIRI on Gemini North. The target is spatially and spectrally resolved into two components: an 8000 K DA white dwarf, and a likely L8 brown dwarf companion, separated by 0.94 . The spectral type of the secondary was determined using standard spectral indices for late L and T dwarfs. The projected orb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Because white dwarfs are the progeny of MS stars with masses of up to 8 M ⊙ , studies of white dwarf binaries can probe the companion mass function over a wide range of (initial) host star masses. Currently, only four white dwarfs are confirmed to have (non‐interacting) substellar companions (Becklin & Zuckerman 1988; Farihi & Christopher 2004; Maxted et al 2006; Steele et al 2009, but see Luhman, Burgasser & Bochanski 2011 for a very low‐mass candidate), and the fraction of white dwarfs with brown dwarf companions appears to be consistent with the low number found around FGK stars (Farihi, Becklin & Zuckerman 2005; Hoard et al 2007).…”
Section: Introductionmentioning
confidence: 88%
“…Because white dwarfs are the progeny of MS stars with masses of up to 8 M ⊙ , studies of white dwarf binaries can probe the companion mass function over a wide range of (initial) host star masses. Currently, only four white dwarfs are confirmed to have (non‐interacting) substellar companions (Becklin & Zuckerman 1988; Farihi & Christopher 2004; Maxted et al 2006; Steele et al 2009, but see Luhman, Burgasser & Bochanski 2011 for a very low‐mass candidate), and the fraction of white dwarfs with brown dwarf companions appears to be consistent with the low number found around FGK stars (Farihi, Becklin & Zuckerman 2005; Hoard et al 2007).…”
Section: Introductionmentioning
confidence: 88%
“…Among their 52 disk candidates, they find six sources (three previously known, and three new) above this flux cutoff, and thus a nominal disk fraction of 1.5%. However, one of these six is a system with an L-type companion (PHL 5038; Steele et al 2009), and another was found to have a neighboring (extragalactic) source contaminating the WISE photometry (Barber et al, 2014). Therefore, this sample yields 1% of white dwarfs with detectable disks, over a range of cooling ages likely identical to Girven et al (2011), for T eff > 8000 K. While this fraction could be somewhat higher, as Debes et al (2011a) also cataloged another dozen white dwarfs with indeterminate-type excesses and photospheres predicted to be above the flux cutoff, the overall survey underscores the need for careful examination and follow up of WISE disk candidates, especially below the 5σ sensitivity.…”
Section: Independent Studies and Infrared Statisticsmentioning
confidence: 99%
“…One of our variable candidates, SDSS J2220−0041, is a known white dwarf plus brown dwarf binary (PHL 5038; Steele et al 2009). The presence of a low-mass companion can, in some cases, cause some optical variability.…”
Section: Sdss J2220−0041 a White Dwarf Plus Brown Dwarf Binarymentioning
confidence: 99%
“…Both these mechanisms require the stars in the binary to be very close, but SDSS J2220−0041 is instead a wide binary system. The two stars in the system are spatially resolved at an angular separation of 0.94'; corresponding to an orbital separation of 55 au (Steele et al 2009). The Stripe 82 data alone does not allow us to identify the nature of the variability or to speculate on a possible connection with the presence of the brown dwarf companion.…”
Section: Sdss J2220−0041 a White Dwarf Plus Brown Dwarf Binarymentioning
confidence: 99%